2011
DOI: 10.1523/jneurosci.2922-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Homeostasis Is Critical for Synaptic Development and Function

Abstract: The ubiquitin-proteasome system (UPS) controls protein abundance and is essential for many aspects of neuronal function. In ataxia (ax J ) mice, profound neurological and synaptic defects result from a loss-of-function mutation in the proteasome-associated deubiquitinating enzyme Usp14, which is required for recycling ubiquitin from proteasomal substrates. Here, we show that transgenic complementation of ax J mice with neuronally expressed ubiquitin prevents early postnatal lethality, restores muscle mass, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 33 publications
7
110
1
Order By: Relevance
“…Notably, all the negative effects observed in the ax J phenotype were attributed to the decreased free ubiquitin levels, resulting ultimately in synaptic dysfunction. Restoring free ubiquitin levels prevented the early death at 8 weeks of age, body weight loss and presynaptic dysfunction observed in the ataxic mice (Chen et al, 2011). The deficit in neurotransmitter release in the ax J mice is in accordance with the results showing that inhibition of Uch-L1, another DUB abundantly expressed in neurons, also decreases free ubiquitin levels, thus increasing the number of synaptic vesicles (Cartier et al, 2009).…”
Section: Role Of Ups In Nervous Systemsupporting
confidence: 83%
“…Notably, all the negative effects observed in the ax J phenotype were attributed to the decreased free ubiquitin levels, resulting ultimately in synaptic dysfunction. Restoring free ubiquitin levels prevented the early death at 8 weeks of age, body weight loss and presynaptic dysfunction observed in the ataxic mice (Chen et al, 2011). The deficit in neurotransmitter release in the ax J mice is in accordance with the results showing that inhibition of Uch-L1, another DUB abundantly expressed in neurons, also decreases free ubiquitin levels, thus increasing the number of synaptic vesicles (Cartier et al, 2009).…”
Section: Role Of Ups In Nervous Systemsupporting
confidence: 83%
“…Increased transcription of endogenous USP14, a DUB demonstrated to maintain monoubiquitin in mice (37)(38)(39)(40), may account for monoubiquitin not being depleted when DmUSP5 is knocked down in developing flies. When we tested whether exogenous USP14 alleviates lethality caused by knockdown of DmUSP5, we found that this was not the case ( Fig.…”
Section: Dmusp5 Knockdown Leads To Increased Conjugated Ubiquitin Spementioning
confidence: 99%
“…Autophagy and the ubiquitin-proteasome system are major pathways for protein degradation in cells. Accumulating evidence has indicated the importance of protein degradation via the ubiquitin-proteasome system, which is mainly responsible for the turnover of short-lived cytosolic proteins, in regulating synaptic growth [13][14][15][16] . Highwire (Hiw), an E3 ubiquitin ligase that mediates key steps in the protein ubiquitination process, negatively governs synaptic growth at the Drosophila NMJ [17,18] .…”
Section: Autophagy In Synaptogenesismentioning
confidence: 99%